2011
DOI: 10.1007/s10750-011-0952-5
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove and coral reef sponge faunas: untold stories about shallow water Porifera in the Caribbean

Abstract: Sponge faunas from coral reefs and mangrove ecosystems in the Caribbean have mostly been studied from an ecological perspective, with researchers considering the effects of physical and biological factors on their species distribution. To discern evolutionary patterns, this study analyzed the systematic composition, taxonomic diversity, and ecological properties (reproductive strategies, size, shape, endosymbiosis) of mangrove and reef sponge assemblages from seven distant Caribbean localities. Species composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
1
8
0
1
Order By: Relevance
“…3b, e) that rarely grows in habitats other than mangrove, most of the sponge fauna in Caribbean mangroves consists of generalist species that, because of their resistance to desiccation, siltation, and salinity stress, are able to colonize this habitat from adjacent reefs and seagrass meadows (see Table 1 for examples of shared species). Nevertheless, these mangrove-colonizing generalists develop abundance patterns different from what they show in adjacent reefs and seagrasses; coupled with the presence of some mangrove specialists, this makes the sponge fauna of mangroves systems across the Caribbean globally distinct (Diaz 2012). Unlike coral reefs, where large tubular, vase, and ramose species dominate, mangroves are rich in thin crusts and thick massive sponges.…”
Section: Mangrove Sponge Aggregationsmentioning
confidence: 94%
“…3b, e) that rarely grows in habitats other than mangrove, most of the sponge fauna in Caribbean mangroves consists of generalist species that, because of their resistance to desiccation, siltation, and salinity stress, are able to colonize this habitat from adjacent reefs and seagrass meadows (see Table 1 for examples of shared species). Nevertheless, these mangrove-colonizing generalists develop abundance patterns different from what they show in adjacent reefs and seagrasses; coupled with the presence of some mangrove specialists, this makes the sponge fauna of mangroves systems across the Caribbean globally distinct (Diaz 2012). Unlike coral reefs, where large tubular, vase, and ramose species dominate, mangroves are rich in thin crusts and thick massive sponges.…”
Section: Mangrove Sponge Aggregationsmentioning
confidence: 94%
“…The species composition of these mangrove-associated sponge communities is very distinct from sponge communities living on nearby reefs (e.g. van Soest 1978, 1980, 1984, Wulff 2004, Diaz 2012, but the mechanisms that underlie this distinction remain uncertain (for review see Wulff 2012). Transplantation experiments of typical reef sponges to roots on off-shore mangrove stands embedded in coral reefs revealed that reef species were able to grow well on roots and compete with typical mangrove sponges in the presence of spongivorous fishes (Wulff 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We transferred 3 sponge pieces to each root; 1 individual of each of the 3 most abundant sponges (Tedania ignis, Lissodendoryx isodictyalis, and Chondrilla caribensis) around Key Largo (Engel & Pawlik 2005). T. ignis is one of the most abundant mangrove sponges in the Caribbean (Diaz & Rützler 2009, Wulff 2009 and references therein, Guerra-Castro et al 2011, Diaz 2012). Each of the 3 sponge individuals was randomly assigned an attachment location (upper, middle, or lower) on each root because the lower (i.e.…”
Section: Predation Susceptibility Experimentsmentioning
confidence: 99%